Long-term storage limits PCR-based analyses of malaria parasites in archival dried blood spots. - Hwang, J; Jaroensuk, J; Leimanis, M; Russell, B; McGready, R; Day, N; Snounou, G; Nosten, F; Imwong, M (BioMed Central, 2012)
BACKGROUND: Blood samples collected in epidemiological and clinical investigations and then stored, often at room temperature, as blood spots dried on a filter paper have become one of the most popular source of material for further molecular analyses of malaria parasites. The dried blood spots are often archived so that they can be used for further retrospective investigations of parasite prevalence, or as new genetic markers come to the fore. However, the suitability of the template obtained from dried blood spots that have been stored for long periods for DNA amplification is not known. METHODS: DNA from 267 archived blood spots collected over a period of 12 years from persons with microscopically confirmed Plasmodium falciparum infection was purified by one of two methods, Chelex and Qiagen columns. These templates were subjected to highly sensitive nested PCR amplification targeting three parasite loci that differ in length and/or copy number. RESULTS: When a 1.6 kb fragment of the parasites' small subunit ribosomal RNA was targeted (primary amplification), the efficiency of P. falciparum detection decreased in samples archived for more than six years, reaching very low levels for those stored for more than 10 years. Positive amplification was generally obtained more often with Qiagen-extracted templates. P. falciparum could be detected in 32 of the 40 negative Qiagen-extracted templates when a microsatellite of about 180 bp was targeted. The remaining eight samples gave a positive amplification when a small region of 238 bp of the higher copy number (20 to 200) mitochondrial genome was targeted. CONCLUSIONS: The average length of DNA fragments that can be recovered from dried blood spots decreases with storage time. Recovery of the DNA is somewhat improved, especially in older samples, by the use of a commercial DNA purification column, but targets larger than 1.5 kb are unlikely to be present 10 years after the initial blood collection, when the average length of the DNA fragments present is likely to be around a few hundred bp. In conclusion, the utility of archived dried blood spots for molecular analyses decreases with storage time.